Impact of Classroom Environment on Student’s Attitude Towards School - LUBNA NAZNEEN; DR. SUMMAYYA HAYAT; DR. JUNAID ATHAR KHAN (Journal of Business & Tourism, 2021)
Current study was undertaken to determine the effect of psychosocial classroom environment on student’s attitude towards school. Using cluster sampling technique 203 students’ including 97 females’ and 107 males, age range 12-14 years were taken from class 7th and 8th of different government and private schools in Peshawar. What Is Happening In This Class? (WIHIC) questionnaire (Fraser, McRobbie & Fisher, 1996) and an Attitude toward School Scale (Anderson, 1999) were administered for data collection. Psychosocial classroom environment was found to be a significant predictor of students’ attitude towards school. There were also some gender differences on different classroom environment variables and their impact on student’s attitude towards school.